Analytical Landau-Devonshire approach of bulk Ferroelectric Phenomena - Loh, Kok Khuan (2016)
Currently static and dynamic behaviour of ferroelectric materials are described either numerically using the Landau-Devonshire (LD) model of phase transitions or various empirical formulae obtained by fitting experimental data of specific ferroelectric substances such as barium titanate, triglycine sulfate and lead titanate. As such ferroelectric phenomena such as switching current transients switching time and polarization relaxation are described by separate empirical formulae but lack a unified description based upon a common theoretical framework.